An All‐Fluorinated Electrolyte Toward High Voltage and Long Cycle Performance Dual‐Ion Batteries. Issue 19 (9th February 2022) - Wang, Yao; Zhang, Yanjun; Dong, Shuyu; Zhou, Wenchong; Lee, Pui‐Kit; Peng, Zehua; Dang, Chaoqun; Sit, Patrick H.‐L.; Guo, Junpo; Yu, Denis Y. W.
Abstract: The dual‐ion battery (DIB) is a promising energy storage system that demonstrates high‐power characteristics and fast‐charging capability. However, conventional electrolytes are not compatible with the high‐voltage graphite cathode and the reactive Li metal anode, thus leading to the poor cycle stability and low Coulombic efficiency of the DIB. Here, an all‐fluorinated electrolyte is reported that can enable a highly stable operation of the graphite||Li DIB up to 5.2 V by forming robust and less‐resistive passivation films on both electrodes to reduce side reactions. The electrolyte allows reversible PF6 – anion insertion/extraction and Li + cation plating/stripping in the graphite||Li battery, achieving stable cycling with 94.5% capacity retention over 5000 cycles at 500 mA g –1, high capacity utilization of 91.8% of the available charge capacity at 50 C (5000 mA g –1 ), and also minimal self‐discharge. At a low temperature of 0 °C, this all‐fluorinated electrolyte exhibits 97.8% of the room temperature reversible capacity, along with ≈100% capacity retention after more than 3000 cycles, at 5 C. This work sheds a new light on the development of fluorinated electrolytes for high voltage and long‐lasting DIBs. Abstract : An all‐fluorinated electrolyte enables reversible PF6 – insertion/extraction in a high‐voltage cathode (5.2 V) and Li + plating/stripping on a reactive Li metal anode. The graphite||Li battery demonstrates stable cycling with 94.5% capacity retention over 5000 cycles, no capacity fading upon 3000 cycles at 0 °C, ultrafast charging capability up to 50 C (5000 mA g –1 ) with 91.8% capacity utilization and a low self‐discharge rate.